A PRISMA-Guided Systematic Review on the Business Performance of Small and Medium Enterprises in Indonesia - Muis, Indra (Journal of Accounting and Finance Management, 2025)
This study aims to systematically review and synthesize recent empirical research on the business performance of Small and Medium Enterprises (SMEs) in Indonesia using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. A systematic literature review was conducted based on articles indexed in the Scopus database. A total of 66 studies published between 2021and 2025 were identified and analysed using a structured PRISMA-based protocol. Inclusion criteria were applied to screen studies based on relevance, language, and context. Thematic synthesis was employed to identify key drivers and constraints affecting SME performance. The analysis reveals that business performance in Indonesian SMEs is predominantly influenced by innovation capability, digital transformation, entrepreneurial orientation, financial literacy, and government policy support. Most studies utilized quantitative approaches and focused on manufacturing and service sectors. However, regional disparities and methodological gaps remain in the existing literature. The findings provide useful insights for SME stakeholders, policymakers, and academic researchers in understanding the determinants of SME performance and identifying under-researched areas for future inquiry. This is one of the first comprehensive reviews applying PRISMA to synthesize literature on SME business performance in the Indonesian context. It highlights current trends, gaps, and future research opportunities.